1998
DOI: 10.1128/aem.64.1.62-67.1998
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of a Polyester Polyurethane-Degrading Enzyme from Comamonas acidovorans TB-35

Abstract: A polyester polyurethane (PUR)-degrading enzyme, PUR esterase, derived from Comamonas acidovorans TB-35, a bacterium that utilizes polyester PUR as the sole carbon source, was purified until it showed a single band in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). This enzyme was bound to the cell surface and was extracted by addition of 0.2%N,N-bis(3-d-gluconamidopropyl)deoxycholamide (deoxy-BIGCHAP). The results of gel filtration and SDS-PAGE showed that the PUR esterase was a monomer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(72 citation statements)
references
References 27 publications
6
66
0
Order By: Relevance
“…Our studies provide the ¢rst evidence of a high-molecular-mass PBSA-degrading bacterium inhabiting a real ecosystem and producing lipase to degrade PBSA. Furthermore, this enzyme exhibited similar characteristics to the polyester^polyurethane-degrading enzyme (PUR esterase) reported previously by us [10]. As reported by us, PUR esterase possesses a hydrophobic substrate surface-binding domain besides a catalytic domain, and PUR degradation occurs in two steps, adsorption to substrate and hydrolysis.…”
Section: Discussionsupporting
confidence: 84%
“…Our studies provide the ¢rst evidence of a high-molecular-mass PBSA-degrading bacterium inhabiting a real ecosystem and producing lipase to degrade PBSA. Furthermore, this enzyme exhibited similar characteristics to the polyester^polyurethane-degrading enzyme (PUR esterase) reported previously by us [10]. As reported by us, PUR esterase possesses a hydrophobic substrate surface-binding domain besides a catalytic domain, and PUR degradation occurs in two steps, adsorption to substrate and hydrolysis.…”
Section: Discussionsupporting
confidence: 84%
“…Pristine films showed a hydrophobic surface with a WCA of 92° (see Table S1 ), which means that it is a non-favorable surface for water-soluble enzyme molecules. In previous studies, it was shown that insoluble PU substrates can be degraded by enzyme molecules which, by an unknown process, attach themselves onto the surface of the insoluble substrates [ 43 ]. After the adhesion process, the enzymatic reaction may rapidly proceed in some cases [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a relatively slow process in which cleavage of polymer backbone by bond scission leads to generation of carbonyl groups (oxidation) which are considered to be utilized by the microorganism as a source of carbon and energy. [11][12][13] There are a few reports showing biodegradation of synthetic polymers including polyethylene, polyurethane, polyvinyl chloride [14][15][16][17][18][19][20] and their microplastic forms. [21][22][23] PS also belongs to a non-biodegradable class of synthetic polymers 12 but very limited data is available on its biodegradation.…”
Section: Introductionmentioning
confidence: 99%